2010
DOI: 10.1007/s12245-010-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges in the provision of ambulance services in New Zealand

Abstract: Emergency Medical Services (EMS) in New Zealand has been serving the society since the first ambulance in 1892. Since then it has developed rapidly following national health system reforms and changes in lifestyle that increase demands and expectations from local communities. Today, the system provides high-quality pre-hospital emergency care. This article will briefly introduce some of the issues facing EMS that will impact the future of this crucial system in New Zealand. These issues include demands because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In the same context, authors [16,20] emphasize that technological advances have driven the steady increase in care complexity and demanding an increasingly high level of attention from health professionals, creating a growing demand for material resources and equipment. Thus, the need for health services to improve the management system for these resources to ensure continuous assistance are necessary for ensuring the quality and quantity of materials and displacement devices such as ambulances, so that professionals can carry out their activities safely, with the appropriate time response for each occurrence requested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same context, authors [16,20] emphasize that technological advances have driven the steady increase in care complexity and demanding an increasingly high level of attention from health professionals, creating a growing demand for material resources and equipment. Thus, the need for health services to improve the management system for these resources to ensure continuous assistance are necessary for ensuring the quality and quantity of materials and displacement devices such as ambulances, so that professionals can carry out their activities safely, with the appropriate time response for each occurrence requested.…”
Section: Discussionmentioning
confidence: 99%
“…Another structure indicator often cited in studies [15,20,23,27] is the continuing education of professionals in the pre-hospital mobile staff, since, in this scenario, it is imperative that professionals have the multi-purpose-oriented training to the reality. Thus, there is the importance of working from the definition of areas of expertise, enabling the integration of different knowledge and expertise and multidisciplinary interaction, contributing to the formation of a professional who adds skills for decision-making, communication, leadership, and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The QA-PHC instrument was developed based on emergency pre-hospital care quality indicators identified by studies in the area (9,(12)(13)(14)(15) . The identification of quality indicators was carried out through an integrative literature review, guided by the following question: What are the quality healthcare indicators used in studies analyzing mobile emergency pre-hospital services?…”
Section: Methodsmentioning
confidence: 99%
“…In New Zealand, it has been shown that there is a relatively high incidence of ambulance use by elderly patients for medical problems that could have been avoided by better primary care. Besides, the increasing number of emergency calls requiring advanced care is a major problem in rural areas as ambulance officers are mainly volunteers 2) . Therefore, the PRIME service plays a crucial role in the management of patients in these areas.…”
Section: General Practice (Gp) and Emergency Department (Ed)mentioning
confidence: 99%